2020
DOI: 10.1177/0846537120967701
|View full text |Cite
|
Sign up to set email alerts
|

2020 MR Safety for Cardiac Devices: An Update for Radiologists

Abstract: Magnetic resonance imaging (MRI) is a unique and powerful diagnostic tool that provides images without ionizing radiation and, at times, can be the only modality to properly assess and diagnose some pathologies. Although many patients will need an MRI in their lifetime, many of them are still being unjustly denied access to it due to what were once considered absolute contraindications, including MR nonconditional pacemakers and implantable cardioverter-defibrillators. However, there are a number of large stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 58 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…In 2020 we were provided with a guideline and performance recommendations. 6 This update explained that MRI in the presence of implantable cardiac devices is much safer than historically thought and can be implemented into routine practice with a few considerations. First, the type of device must be considered as a few devices including permanent epicardial leads, temporary pacemakers, ventricular assist devices, and pulmonary artery monitoring devices remain contraindicated due to the potential for adverse events.…”
Section: Safetymentioning
confidence: 99%
“…In 2020 we were provided with a guideline and performance recommendations. 6 This update explained that MRI in the presence of implantable cardiac devices is much safer than historically thought and can be implemented into routine practice with a few considerations. First, the type of device must be considered as a few devices including permanent epicardial leads, temporary pacemakers, ventricular assist devices, and pulmonary artery monitoring devices remain contraindicated due to the potential for adverse events.…”
Section: Safetymentioning
confidence: 99%
“…The authors reported that only 1% of their studies were nondiagnostic. 1 Others have reported a 90% diagnostic rate for thoracic and cardiac MRIs in patients with CIEDs. 2 We have found that our success rate is closer to 85-90%.…”
mentioning
confidence: 99%
“…In their article ''2020 MR Safety for Cardiac Devices: An Update for Radiologists,'' Lebel et al review the current literature on cardiac magnetic resonance (CMR) in patients with cardiovascular implantable electronic devices (CIEDs) while providing a framework on how to safely image these patients. 1 They share their experience with performing CMR on CIED patients with specific emphasis on safety and work-flow. 1 With the growing number of patients with CIEDs and the increasing utility of CMR, we have also experienced an increased demand for CMR in patients with CIEDs.…”
mentioning
confidence: 99%
See 2 more Smart Citations